2009
DOI: 10.1002/pmj.20104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamics of Value and Fit: Insights from Project Management

Abstract: The strategic management literature has struggled with how to recognize, measure, and even understand the concept of “fit” between strategy, structure, and environment. Nevertheless, the concept of fit was fundamentally important from the beginning of the Value of Project Management project. In this article, we compare the “fit” construct defined by Miles and Snow (1984) with our concerns with value direction (Thomas & Mullaly, 2008). A comparative analysis of these two constructs provides insights into how bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…We also recognize that managers with their cache of personality dimensions labor within organizations that may have systems that affect project outcomes. The systems we contend that are critical for project success are structure (Mullaly & Thomas, 2009), organizational maturity (Zqikael, Levin, & Rad, 2008), and incentive systems (Yang & Chen, 2009). These systems have the potential to moderate (Strang, 2011) the theoretical relationships between the independent variables of personality dimensions and dependent variable of project success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also recognize that managers with their cache of personality dimensions labor within organizations that may have systems that affect project outcomes. The systems we contend that are critical for project success are structure (Mullaly & Thomas, 2009), organizational maturity (Zqikael, Levin, & Rad, 2008), and incentive systems (Yang & Chen, 2009). These systems have the potential to moderate (Strang, 2011) the theoretical relationships between the independent variables of personality dimensions and dependent variable of project success.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational structures, beginning with the purely functional organization to the projectized organization, have been presented in A Guide to the Project Management Body of Knowledge (PMBOK ® Guide) —Fifth Edition (PMI, 2013). The importance of organizational structures and their effects on project management has received attention (Mullaly & Thomas, 2009; Procca, 2008; Laslo & Goldberg, 2008; Wellman, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is at odds with extant research in project management as(Cooke-Davies, Crawford, and Lechler, 2009)suggest that project management capabilities need to be aligned with overall organizational strategic intent in order to generate value. This implies that project capabilities developed by organizations may vary even within a given industry as organizational approach will determine the capabilities developed, not the maturity models adopted (Mullaly and Thomas, 2009). Further, comparative research (Graham, 1999) demonstrates differing project approaches by industry based on systems for allocating value and managing delivery.…”
Section: Critical Evaluation Of Maturity Modelsmentioning
confidence: 99%
“…The contingency approach suggests that performance of organizations is attributable to the fit between a set of contingencies. 12,36 In a similar vein, the introduction of new, contextual variable(s) is required in PRM research. Many studies had identified various "project characteristics" as a possible contextual factor.…”
Section: Project Complexity and The Moderation Modelmentioning
confidence: 99%